Nível de atividade física no lazer em usuários do Sistema Único de Saúde - Codogno, Jamile Sanches [UNESP]; Turi, Bruna Camilo [UNESP]; Fernandes, Rômulo Araújo [UNESP]; Monteiro, Henrique Luiz [UNESP] (My University, 2012)
Although leisure physical activity has been investigated in general population, there is absence of data in Brazilian Public Health System about this issue. Thus, the purpose of this study was to analyze in patients attended by Public Health System the prevalence of leisure physical activity, as well as, to identify its correlates and associated diseases. Sample was composed by 963 patients (707 female and 256 male) randomly selected at five basic healthcare units. Leisure physical activity was assessed by Baecke’s questionnaire and subjects with ≥180 and ≥240 minutes per week were classified as sufficiently active. General and central obesity were assessed by body mass index and waist circumference, respectively. Diseases of high occurrence were classified according CID-10. There was low rate of physically active subjects in leisure time (14.8%),but high rate of abdominal obesity (70.1%) and orthopedic diseases (72.1%). Physically active subjects in leisure time had lower occurrence of orthopedic diseases (OR= 0.60 [OR95%CI: 0.37 – 0.98]). The same pattern of association was observed for central obesity (OR= 0.35 [OR95%CI: 0.19 – 0.65]). It is low the rate of physically active in leisure time at Brazilian Public Health System, which is associated with orthopedic diseases.

Embora se investigue a atividade física no lazer na população em geral, muito pouco se sabe sobre está variável entre pacientes do Sistema Único de Saúde. Assim, o objetivo deste estudo foi analisar o nível de atividade física no lazer de pacientes atendidos na rede publica de saúde de Bauru-SP, bem como, identificar alguns de seus determinantes e sua associação com alguns agravos à saúde. A amostra foi composta por 963 pacientes (707 mulheres e 256 homens) selecionados aleatoriamente em cinco unidades básicas de saúde. As atividades físicas no lazer foram avaliadas pelo questionário de Baecke e indivíduos que reportaram ≥180 ou ≥240 minutos por semana de atividades físicas foram considerados ativos e muito ativos. Obesidade geral e obesidade central foram identificadas por valores de índice de massa corporal e circunferência de cintura, respectivamente. As doenças de maior ocorrência foram agrupadas segundo o CID-10. Houve baixa prática suficiente de atividade física no lazer (14,8%), mas elevada taxa de obesidade abdominal (70,1%) e doenças do aparelho osteomuscular e do tecido conjuntivo (72,1%). Indivíduos fisicamente ativos no lazer apresentaram menor ocorrência de doenças do aparelho osteomuscular e do tecido conjuntivo (OR= 0.60 [ORIC95%: 0.37 – 0.98]). A mesma associação foi observada para o sexo feminino no que diz respeito à obesidade abdominal (OR= 0.35 [ORIC95%: 0.19 – 0.65]). É baixa a prática suficiente de física no lazer entre pacientes do Sistema Único de Saúde, a qual está associada à menor ocorrência de doenças do aparelho osteomuscular e do tecido conjuntivo.
Level of leisure physical activity in users of the Brazilian public health system
Keywords: Physical activity; Primary healthcare; Epidemiological study; Brazil; Atividade motora; Atenção primária à saúde; Estudo epidemiológico; Brasil